2023
DOI: 10.3390/children10091534
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Handwriting Performance of Children with Developmental Coordination Disorder (DCD) Using Computerized Visual Feedback

Rachel Bartov,
Michael Wagner,
Nir Shvalb
et al.

Abstract: Recent studies have analyzed the writing metrics of children with developmental coordination disorder (DCD) using computerized systems. To date, the use of computerized visual feedback to improve handwriting has not been investigated. This study aimed to examine the effects of computerized visual feedback on handwriting performance in time, spatial orientation, and pressure indices for children with DCD. Twenty-seven children aged 7 to 12 years with DCD assessed by the Movement Assessment Battery for Children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 58 publications
(103 reference statements)
0
0
0
Order By: Relevance
“…Four of the RCT papers were poorly reported and consequently, the risk of bias was unclear in several domains (44)(45)(46)(47). Poor methodology in all four crossover trials resulted in a moderate-high risk of bias (49)(50)(51)(52). The non-randomized trials revealed unclear reporting of methods with some concerns about the fidelity of the interventions provided, however, most other domains revealed a low risk of bias (31, 53, 54).…”
Section: Quality Of Included Studies: Risk Of Biasmentioning
confidence: 98%
See 4 more Smart Citations
“…Four of the RCT papers were poorly reported and consequently, the risk of bias was unclear in several domains (44)(45)(46)(47). Poor methodology in all four crossover trials resulted in a moderate-high risk of bias (49)(50)(51)(52). The non-randomized trials revealed unclear reporting of methods with some concerns about the fidelity of the interventions provided, however, most other domains revealed a low risk of bias (31, 53, 54).…”
Section: Quality Of Included Studies: Risk Of Biasmentioning
confidence: 98%
“…Six RCTs, represented in seven articles (42)(43)(44)(45)(46)(47)(48), four randomized crossover design trials (49)(50)(51)(52) and three quasiexperimental designs (31, 53, 54) were included in the systematic review. Eight trials assessed internal FOA compared to external FOA, one trial assessed KOR and the remaining four trials were included due to providing augmented feedback delivered via technology in the intervention group, which was tested against traditional therapy.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations